PSYCHOLOGY OF LANGUAGE MECHANIZMS AND SPEECH DEVELOPMENT METHODS - Farida, Orazakynkyzy; Almazhai, Yegenissova; Rikhsibay, Mamedov; Elmira, Montanai; Gulnar, Aizhanova; Assel, Almabekova (International Journal of Psychosocial Rehabilitation, 2020)
Psycholinguistics, in another word psychology of language, is a subsection of study uniting the disciplines of psychology and linguistics. Psycholinguistics is about how we produce and recognize the speech and functioning of the brain to process the language. The cognitive processes of a language can shortly be called as memory, thinking, learning and perception. It came forward as a new discipline by Chomskyan revolution. Acquisition, comprehension and production are the main processes of it. The knowledge we need to be able to use the language and the cognitive processes constitutes the backbones of psycholinguistics. It studies the mental faculties of how man’s mind perceives, develops and produces spoken and written communication. The specific topics it analyses are phonetics, semantics, pragmatics, syntax, phonolgy and morphology. Emerging as a reaction to Behaviorist Theory of the B.F. Skinner who considered all forms of learning as a dichotomy of positive and negative reinforcement, Noam Chomsky put forth that human being is innately programed for languages and all the required neurobiological factors enabling us to acquire, use and comprehend the language cognitively exist in us. So, in this sub-field of science of linguistics, what makes it possible to generate meaningful sentences out of lexis and grammatical components cognitively forms the rationale of psycholinguistics.